2019
DOI: 10.1108/ec-10-2018-0477
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of high-performance BEM and investigation on convergence of GMRES in local stress analysis of slender real thin-plate beams

Abstract: Purpose Based on the error analysis, the authors proposed a new kind of high accuracy boundary element method (BEM) (HABEM), and for the large-scale problems, the fast algorithm, such as adaptive cross approximation (ACA) with generalized minimal residual (GMRES) is introduced to develop the high performance BEM (HPBEM). It is found that for slender beams, the stress analysis using iterative solver GMRES will difficult to converge. For the analysis of slender beams and thin structures, to enhance the efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, as the singularities of the kernel function in the boundary integral equation (BIE), the computational accuracy of weak singular integral directly affects the final results, so additional processing schemes must be given to remove these singularities to ensure the successful solution of BEM. Especially for thin-structural problems, poorly shaped elements (such as elements with large angles or narrow lengths) will appear in the discrete geometric model of thin structure [12][13][14], which will seriously affect the accuracy of singular and near singular integrals. Many works have been demonstrated that the near singular integrals can be accurately evaluated by analytical and semi-analytical methods [15,16], Sinh and other nonlinear transformation methods [4,[17][18][19], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the singularities of the kernel function in the boundary integral equation (BIE), the computational accuracy of weak singular integral directly affects the final results, so additional processing schemes must be given to remove these singularities to ensure the successful solution of BEM. Especially for thin-structural problems, poorly shaped elements (such as elements with large angles or narrow lengths) will appear in the discrete geometric model of thin structure [12][13][14], which will seriously affect the accuracy of singular and near singular integrals. Many works have been demonstrated that the near singular integrals can be accurately evaluated by analytical and semi-analytical methods [15,16], Sinh and other nonlinear transformation methods [4,[17][18][19], etc.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain high calculation accuracy, the integral element needs to be subdivided into several integral blocks with good shape. And there are many element subdivision methods, such as the singular points directly connected to the element vertexes [12], interval block method [12], tree structure methods [25], etc. When these subdivision methods are employed, some integral blocks with poor shape (such as the integral blocks with large angle and large aspect ratio) will be subdivided, which increases the difficulty in dealing with singular integral and decrease the computational accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…To deal with this issue an MPI parallel algorithm described in [5,15] was incorporated allowing for an efficient solution. For this purpose, it is also possible to use adaptive cross approximation, also known as hierarchical matrices [16][17][18] and other high-performance BEM implementations, such as those in [19,20]. However, in BESLE we adopt the strategy of finding an adequate balance between the number of DOFs and subdomains under consideration and this mean that very large scale problems are now feasible to be treated without any additional arduous method.…”
Section: Introductionmentioning
confidence: 99%